\(\frac{3}{\sqrt{x}-2}\)  (đkxđ: \(x\ne4\),  
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

26 tháng 2 2020

M = \(\frac{2\sqrt{x}-9x}{x-5\sqrt{x}+6}-\frac{\sqrt{x}+3}{\sqrt{x}-2}-\frac{2\sqrt{x}+1}{3-\sqrt{x}}\)

    =\(\frac{2\sqrt{x}-9}{x-5\sqrt{x}+6}-\frac{\left(\sqrt{x}+3\right)\left(3-\sqrt{x}\right)+\left(\sqrt{x}-2\right)\left(2\sqrt{x}+1\right)}{\left(\sqrt{x}-2\right)\left(3-\sqrt{x}\right)}\)

    =\(\frac{2\sqrt{x}-9}{x-5\sqrt{x}+6}+\frac{9-x+2x-3\sqrt{x}}{x-5\sqrt{x}+6}\)

    =\(\frac{x-\sqrt{x}}{x-5\sqrt{x}+6}\)

7 tháng 8 2017

1. \(N=\left(\frac{2+\sqrt{x}}{2-\sqrt{x}}-\frac{2-\sqrt{x}}{2+\sqrt{x}}-\frac{4x}{x-4}\right):\frac{\sqrt{x}-3}{2\sqrt{x}-x}\)

\(N=\left(\frac{2+\sqrt{x}}{2-\sqrt{x}}-\frac{2-\sqrt{x}}{2+\sqrt{x}}+\frac{4x}{\left(2+\sqrt{x}\right)\left(2-\sqrt{x}\right)}\right):\frac{\sqrt{x}-3}{\sqrt{x}\left(2-\sqrt{x}\right)}\)

\(N=\left(\frac{\left(2+\sqrt{x}\right)^2-\left(2-\sqrt{x}\right)^2+4x}{\left(2+\sqrt{x}\right)\left(2-\sqrt{x}\right)}\right):\frac{\sqrt{x}-3}{\sqrt{x}\left(2-\sqrt{x}\right)}\)

\(N=\left(\frac{4+4\sqrt{x}+x-4+4\sqrt{x}-x+4x}{\left(2+\sqrt{x}\right)\left(2-\sqrt{x}\right)}\right):\frac{\sqrt{x}-3}{\sqrt{x}\left(2-\sqrt{x}\right)}\)

\(N=\left(\frac{8\sqrt{x}+4x}{\left(2-\sqrt{x}\right)\left(2+\sqrt{x}\right)}\right).\frac{\sqrt{x}\left(2-\sqrt{x}\right)}{\sqrt{x}-3}\)

\(N=\frac{4\sqrt{x}\left(2+\sqrt{x}\right)}{\left(2+\sqrt{x}\right)\left(2-\sqrt{x}\right)}.\frac{\sqrt{x}\left(2-\sqrt{x}\right)}{\sqrt{x}-3}\)

\(N=\frac{4x}{x-3}\)

Vậy \(N=\frac{4x}{x-3}\)với \(x>0,x\ne4,x\ne9\)

2.Với \(x>0,x\ne4,x\ne9\)

Ta có \(N< 0\)\(\Leftrightarrow\frac{4x}{x-3}< 0\)\(\Leftrightarrow x-3< 0\)(Vì \(x>0\Leftrightarrow4x>0\)\(với\forall x\))\(\Leftrightarrow x< 3\)

Vậy ..........

3. Với \(x>0,x\ne4,x\ne9\)

Ta có \(\left|N\right|=1\Leftrightarrow\left|\frac{4x}{x-3}\right|=1\Leftrightarrow\orbr{\begin{cases}\frac{4x}{x-3}=1\\\frac{4x}{x-3}=1\end{cases}}\)\(\Leftrightarrow\orbr{\begin{cases}4x=3-x\\4x=x-3\end{cases}}\)\(\orbr{\begin{cases}x=\frac{3}{5} \left(N\right)\\x=-1\left(N\right)\end{cases}}\)

Vậy ...............

2 tháng 7 2015

câu 2:\(\Leftrightarrow\frac{\sqrt{x}-2}{\sqrt{x}+1}.\left(\sqrt{x}+1\right)=m\left(x+1\right)-2\Leftrightarrow\sqrt{x}-2-mx-m+2=0\Leftrightarrow\sqrt{x}=m\left(x+1\right)\Leftrightarrow m=\frac{\sqrt{x}}{x+1}\)

vì x>=0 =>x+1>0 \(\sqrt{x}\ge0\)=> m phải >=0

\(x\ne4\Rightarrow x+1\ne5;\sqrt{x}\ne2\Rightarrow m\ne\frac{2}{5}\)

\(x\ne9\Rightarrow x+1\ne10;\sqrt{x}\ne3\Rightarrow m\ne\frac{3}{10}\)

 

 

 

26 tháng 2 2020

a, M=\(\frac{2\sqrt{x}-9-\left(\sqrt{x}+3\right)\left(\sqrt{x}-3\right)+\left(2\sqrt{x}+1\right)\left(\sqrt{x}-2\right)}{\left(\sqrt{x}-2\right)\left(\sqrt{x}-3\right)}\)(ĐKXD: x>0, x#4, x#9)

=\(\frac{2\sqrt{x}-9-x+9+2x-4\sqrt{x}+\sqrt{x}-2}{\left(\sqrt{x}-2\right)\left(\sqrt{x}-3\right)^{ }}\)=\(\frac{x-\sqrt{x}-2}{\left(\sqrt{x}-2\right)\left(\sqrt{x}-3\right)}\)=\(\frac{\sqrt{x}+1}{\sqrt{x}-3}\)

Vậy.....

b, ta có x=11-6\(\sqrt{2}\)=\(\left(3-\sqrt{2}\right)^2\)

Thay vào M ta đươc:

M=\(\frac{\sqrt{\left(3-\sqrt{2}\right)^2}+1}{\sqrt{\left(3-\sqrt{2}\right)^2}-3}\)=\(\frac{3-\sqrt{2}+1}{3-\sqrt{2}-3}=\frac{4-\sqrt{2}}{-\sqrt{2}}=1-2\sqrt{2}\)

c,Để M<1<=> \(\frac{\sqrt{x}+1}{\sqrt{x}-3}\)<1 <=> \(\frac{\sqrt{x}+1}{\sqrt{x}-3}\)-1<0<=> \(\frac{4}{\sqrt{x}-3}\)<0<=> x<9(t/m x#9) mà x>0, x#4 => 0<x<9 và x#4

Vậy....

d, Để M∈Z <=> \(\frac{\sqrt{x}+1}{\sqrt{x}-3}\)∈Z<=>\(1+\frac{4}{\sqrt{x}-3}\)∈Z<=>\(\frac{4}{\sqrt{x}-3}\)∈Z<=> 4⋮\(\sqrt{x}-3\)<=>\(\sqrt{x}-3\)∈Ư(4)={\(\pm\)1,\(\pm\)2,\(\pm\)4}

<=>\(\sqrt{x}\) ∈ {2,4,5,1,7}

<=>x ∈ {4,16,25,1,49} mà x#4

=> x∈ {16,25,1,49}

vậy..

30 tháng 10 2020

a) Ta có: \(\frac{a-b}{\sqrt{a}-\sqrt{b}}-\frac{\sqrt{a^3}-\sqrt{b^3}}{a-b}\)

\(=\frac{\left(\sqrt{a}-\sqrt{b}\right)\left(\sqrt{a}+\sqrt{b}\right)}{\sqrt{a}-\sqrt{b}}-\frac{\left(\sqrt{a}-\sqrt{b}\right)\left(a+\sqrt{ab}+b\right)}{\left(\sqrt{a}-\sqrt{b}\right)\left(\sqrt{a}+\sqrt{b}\right)}\)

\(=\frac{\left(\sqrt{a}+\sqrt{b}\right)^2}{\sqrt{a}+\sqrt{b}}-\frac{a+\sqrt{ab}+b}{\sqrt{a}+\sqrt{b}}\)

\(=\frac{a+2\sqrt{ab}+b-a-\sqrt{ab}-b}{\sqrt{a}+\sqrt{b}}\)

\(=\frac{\sqrt{ab}}{\sqrt{a}+\sqrt{b}}\)

b)Sửa đề: \(\frac{\left(\sqrt{a}+\sqrt{b}\right)^2-4\sqrt{ab}}{\sqrt{a}-\sqrt{b}}-\frac{a\sqrt{b}+b\sqrt{a}}{\sqrt{ab}}\)

Ta có: \(\frac{\left(\sqrt{a}+\sqrt{b}\right)^2-4\sqrt{ab}}{\sqrt{a}-\sqrt{b}}-\frac{a\sqrt{b}+b\sqrt{a}}{\sqrt{ab}}\)

\(=\frac{\left(\sqrt{a}-\sqrt{b}\right)^2}{\left(\sqrt{a}-\sqrt{b}\right)}-\frac{\sqrt{ab}\left(\sqrt{a}+\sqrt{b}\right)}{\sqrt{ab}}\)

\(=\sqrt{a}-\sqrt{b}-\sqrt{a}-\sqrt{b}\)

\(=-2\sqrt{b}\)

c) Ta có: \(\left(\frac{1}{\sqrt{a}-1}-\frac{1}{\sqrt{a}}\right):\left(\frac{\sqrt{a}+1}{\sqrt{a}-2}-\frac{\sqrt{a}+2}{\sqrt{a}-1}\right)\)

\(=\left(\frac{\sqrt{a}}{\sqrt{a}\left(\sqrt{a}-1\right)}-\frac{\sqrt{a}-1}{\sqrt{a}\left(\sqrt{a}-1\right)}\right):\left(\frac{\left(\sqrt{a}+1\right)\left(\sqrt{a}-1\right)}{\left(\sqrt{a}-2\right)\left(\sqrt{a}-1\right)}-\frac{\left(\sqrt{a}+2\right)\left(\sqrt{a}-2\right)}{\left(\sqrt{a}-2\right)\left(\sqrt{a}-1\right)}\right)\)

\(=\frac{1}{\sqrt{a}\left(\sqrt{a}-1\right)}:\frac{a-1-a+4}{\left(\sqrt{a}-2\right)\left(\sqrt{a}-1\right)}\)

\(=\frac{1}{\sqrt{a}\left(\sqrt{a}-1\right)}\cdot\frac{\left(\sqrt{a}-2\right)\left(\sqrt{a}-1\right)}{3}\)

\(=\frac{\sqrt{a}-2}{3\sqrt{a}}\)

d) Ta có: \(\left(\frac{a\sqrt{a}+b\sqrt{b}}{\sqrt{a}+\sqrt{b}}-\sqrt{ab}\right)\left(\frac{\sqrt{a}+\sqrt{b}}{a-b}\right)^2\)

\(=\left(\frac{\left(\sqrt{a}+\sqrt{b}\right)\left(a-\sqrt{ab}+b\right)}{\left(\sqrt{a}+\sqrt{b}\right)}-\sqrt{ab}\right)\left(\frac{\left(\sqrt{a}+\sqrt{b}\right)}{\left(\sqrt{a}+\sqrt{b}\right)\left(\sqrt{a}-\sqrt{b}\right)}\right)^2\)

\(=\left(a-\sqrt{ab}+b-\sqrt{ab}\right)\cdot\left(\frac{1}{\sqrt{a}-\sqrt{b}}\right)^2\)

\(=\left(a-2\sqrt{ab}+b\right)\cdot\frac{1}{\left(\sqrt{a}-\sqrt{b}\right)^2}\)

\(=\frac{\left(\sqrt{a}-\sqrt{b}\right)^2}{\left(\sqrt{a}-\sqrt{b}\right)^2}=1\)

e) Ta có: \(\left(\frac{\sqrt{x}}{3+\sqrt{x}}+\frac{x+9}{9-x}\right):\left(\frac{3\sqrt{x}+1}{x-3\sqrt{x}}-\frac{1}{\sqrt{x}}\right)\)

\(=\left(\frac{\sqrt{x}\left(3-\sqrt{x}\right)}{\left(3+\sqrt{x}\right)\left(3-\sqrt{x}\right)}+\frac{x+9}{\left(3+\sqrt{x}\right)\left(3-\sqrt{x}\right)}\right):\left(\frac{3\sqrt{x}+1}{\sqrt{x}\left(\sqrt{x}-3\right)}-\frac{\sqrt{x}-3}{\sqrt{x}\left(\sqrt{x}-3\right)}\right)\)

\(=\frac{3\sqrt{x}+9}{\left(3+\sqrt{x}\right)\left(3-\sqrt{x}\right)}:\frac{3\sqrt{x}+1-\sqrt{x}+3}{\sqrt{x}\left(\sqrt{x}-3\right)}\)

\(=\frac{3\left(\sqrt{x}+3\right)}{-\left(\sqrt{x}-3\right)\cdot\left(\sqrt{x}+3\right)}\cdot\frac{\sqrt{x}\left(\sqrt{x}-3\right)}{2\left(\sqrt{x}+2\right)}\)

\(=\frac{-3\sqrt{x}}{2\sqrt{x}+4}\)